Potensi dan Risiko Terjadinya Tindak Pidana Pencucian Uang di Perdagangan Karbon - Adiwarman, Adiwarman (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2024)
Climate change is a global issue with visible impacts such as rising sea levels, heat waves in temperate countries, mutations of certain viruses, and melting ice in the Arctic. The primary solution to this problem is reducing greenhouse gas emissions through domestic efforts on various projects and additional mechanisms such as carbon trading. However, as an innovation in the financial services sector, carbon trading poses risks and potential for money laundering (ML) use. This study aims to provide an overview of current carbon trading practices and discuss the potential for using carbon trading for ML in Indonesia. It also aims to address relevant legal principles and issues. The study employs descriptive-analytical and normative methods to identify ML potential and uncover substantive issues within existing legal provisions. The results reveal that the mechanisms of using carbon credits and rights are vulnerable to ML use in and outside the Carbon Exchange (primary market). Moreover, the underdeveloped state of trading systems, institutions, legal provisions, transparency, and supervision exacerbates this. Prevention measures include implementing Know Your Customer principles and reporting suspicious financial transactions. Law enforcement refers to the provisions of Articles 3, 4, 5, and 6 of the Money Laundering Law.